New Roles for Photoexcited Eosin Y in Photochemical Reactions. Issue 2 (27th November 2018) - Yan, Dong‐Mei; Chen, Jia‐Rong; Xiao, Wen‐Jing
Abstract: Neutral eosin Y‐derived photoexcited states have been found to serve as photoacids and direct hydrogen atom transfer (HAT) catalysts in the activation of glycals and C−H bonds, respectively. These studies pave the way for further use of eosin Y in photochemical synthesis. Abstract : New sides of eosin Y : Neutral eosin Y‐derived photoexcited states have been found to serve as photoacids and direct hydrogen atom transfer (HAT) catalysts in the activation of glycals and C−H bonds, respectively. These studies pave the way for further use of eosin Y in photochemical synthesis.